2021
DOI: 10.1021/acsomega.0c05887
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Studies on the Structure–Performance Relationships of Phenothiazine-Based Organic Dyes for Dye-Sensitized Solar Cells

Abstract: A D–A−π–A dye ( PTZ-5 ) has been synthesized by introducing a benzothiadiazole (BTD) unit as an auxiliary acceptor in a phenothiazine-based D−π–A dye( PTZ-3 ) to broaden its spectral response range and improve the device performance. Photophysical properties indicate that the inclusion of BTD in the PTZ-5 effectively red-shifted the absorption spectra by reducing the E gap . However, the device measurements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…The reduction of the molar extinction coefficient for B2–B4 and B7–B9 might also be caused by the increase of dihedral angles, which hinder the electron flow along the quinoidal π-conjugation system. 24…”
Section: Resultsmentioning
confidence: 99%
“…The reduction of the molar extinction coefficient for B2–B4 and B7–B9 might also be caused by the increase of dihedral angles, which hinder the electron flow along the quinoidal π-conjugation system. 24…”
Section: Resultsmentioning
confidence: 99%
“…Although the original ruthenium(II)-polypyridyl chromophores used in DSSCs, such as N3 [6] and N719 [7], have mostly remained as gold standard dyes due to their large conversion efficiencies [8], their only moderate extinction coefficients and the use of a rare and expensive noble metal has led to the extensive search for highly efficient metal-free dyes. These metal-free dyes offer, in addition to the lower cost of production, easier and greater synthetic versatility and tunable optical and electrochemical properties through structural modification, as demonstrated by the extremely wide array of compounds explored over the years [9][10][11]. Despite being mostly overshadowed by their inorganic counterparts, in recent years comparable or even superior performances have been achieved by metalfree chromophores, such as bulky indoline-quinoxaline dyes (10.65%) [12], tetrathioacene dyes (10.1%) [13] and more elaborate polycyclic aromatic push-pull dyes (12.6%) [14], all employing a Co(II/III) complex as redox shuttle.…”
Section: Introductionmentioning
confidence: 99%
“…So far, many electron-rich D units with various moieties such as phenylamine, phenothiazine, , phenoxazine, , and carbazole have been developed. In this respect, Xie and co-workers have synthesized a series of porphyrin sensitizers containing triphenylamine and phenothiazine as the electron-donating unit, which show excellent performance. , Meanwhile, a series of studies demonstrated that the flexible introduction of alkoxy or alkyl chains into D units, the β-position, and the acceptor unit was conducive to anti-aggregation and thus improved the short-circuit current densities ( J sc ) and PCE. , Furthermore, the electron-deficient moieties, such as benzothiadiazole (BTD), , benzotriazole, and 3,4-ethylenedioxythienylene have also been studied in developing porphyrin sensitizers. Among these auxiliary acceptors, BTD has been proven to be an excellent construction …”
Section: Introductionmentioning
confidence: 99%
“…7,8 Meanwhile, a series of studies demonstrated that the flexible introduction of alkoxy or alkyl chains into D units, the β-position, and the acceptor unit was conducive to anti-aggregation and thus improved the short-circuit current densities (J sc ) and PCE. 17,27−31 Furthermore, the electron-deficient moieties, such as benzothiadiazole (BTD), 35,36 benzotriazole, 37 and 3,4-ethylenedioxythienylene 38 have also been studied in developing porphyrin sensitizers. Among these auxiliary acceptors, BTD has been proven to be an excellent construction.…”
Section: ■ Introductionmentioning
confidence: 99%